2020
DOI: 10.1177/1010539520956411
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Quality of Life Among Productive Age in the General Population: A Cross-Sectional Study of Family Life Survey in Indonesia

Abstract: A large number of productive age populations in Indonesia are tagged reliable human resources, assuming they have a good quality of life (QoL). This study aims to examine the determinant factors related to QoL based on the 2014 Indonesia Family Life Survey. This is a population-based cross-sectional study comprising 13 368 participants aged 15 to 64 years from 23 provinces. The analysis was carried out to construct a composite indicator of QoL. The result showed that the low prevalence of 54% among the general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 29 publications
1
9
1
5
Order By: Relevance
“…The results of this study support previous findings, showing that a good education is able to lower or maintain emotional stress [28], [30]. People with good knowledge can control his psychological health compared to those who have no knowledge [27].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The results of this study support previous findings, showing that a good education is able to lower or maintain emotional stress [28], [30]. People with good knowledge can control his psychological health compared to those who have no knowledge [27].…”
Section: Discussionsupporting
confidence: 90%
“…Good education can lower both physical stress and emotional stress [30], lead to proper jobs and activities, and especially in terms of the economy [31], [32]. These findings indicated that education plays an important role in influencing the specific and general symptoms of psychological, social, and emotional activities [28]. On the one hand, formal education offers the opportunity to acquire knowledge and skills that will serve as human capital, which is related to productivity and success in the labor market to obtain a high return on investment in education [33].…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…7 items of community participation: arisan, community meeting, voluntary labor, program to improve the village, youth group activity, : 25-35, 36-45, 46-55 years), marital status (Cov4: unmarried, single and married), length of education (DL06: ≤ 6, 7-9, ≥ 9 years), and primary activities during the past week (TK01; employed women, unemployed women). The healthrelated quality of life instrument in this study had been used successfully in a similar study (Yuniati & Kamso, 2021).…”
Section: Methodsmentioning
confidence: 99%